Design Interleaved Full Bridge Circuit DC-DC Converter With Fuel Cell Power Source On Hybrid Trains - Miftaks, Taufik Iqbal; Muslim, Muhammad Azis; Rusli, Mochammad (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2024)
Nowadays, electric trains are experiencing a transition from diesel fuel to renewable energy. Hybrid electric trains can prove progress from renewable energy, even though they require more than one energy source such as fuel cells and batteries, because renewable energy cannot stand alone. This results in an increase in voltage on the Fuel Cell (FC) which can have an impact on current density and a decrease in voltage, thus requiring a protected DC-DC Converter type circuit to obtain ideal and dynamic condition characteristics. To overcome this problem, the IFBC (Interleaved Full Bridge Circuit) DC-DC Converter is highly recommended as a voltage regulator. There are several methods used to regulate MOSFET’s which in this case affect the IFBC DC DC Converter settings, one of which is the SMC (Sliding Mode Control) method. SMC is a type of non-linear control that functions functionally to control variable structures. However, the application of SMC requires a considerable switching frequency, which has the potential to cause component loss, therefore the switching frequency needs to be limited to that range. To overcome this problem, a method is needed to identify the IFBC output voltage control process using the SMC method in Fuel Cell applications and the software which is considered the most efficient in carrying out this, namely SIMULINK MATLAB software.